PROFIL STRUKTUR KOMUNITAS LAMUN DI PERAIRAN PANTAI KELAPA INDAH DESA MAHU KECAMATAN SAPARUA TIMUR SEBAGAI SUMBER PEMBELAJARAN BIOLOGI - Tuapattinaya, Prelly; Pattiasina, Eifan Boyke; Pattipeilohy, Johana; Sahetapy, Marcelino; Wattimena, Chilf (Program Studi Pendidikan Biologi FKIP Unpatti, 2023)
Background: Seagrass is a higher plant (Anthophyta) that lives and grows immersed in the marine environment; have vessels, have rhizomes, have roots, and reproduce generatively (seeds) and vegetatively. Seagrass is one of the natural resource ecosystem plants that lives in shallow waters and has many benefits for biota associated with the surrounding environment. Several studies related to seagrass ecosystems have been carried out in Maluku waters, but there are no records regarding the structural profile of seagrass communities on Saparua Island. Methods: This research is descriptive research. Descriptive research is used to reveal information about hydrological conditions, species composition, species diversity. This research was conducted in the waters of Kelapa Indah Beach, Mahu Village, Saparua District Results: The conditions of environmental physical and chemical factors with a temperature of 280C, salinity 31 ‰, pH 7.3, and Dissolved Oxygen 6 mg/L in the waters of Mahu village are sufficient to support the growth and spread of seagrass. Composition of the types of seagrass found in the coastal waters of Mahu village are 5 types and Conclusion: The level of seagrass diversity in Mahu village waters is classified as moderate.